2007
DOI: 10.1007/s00276-007-0238-9
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the distance and angle between the aorta and superior mesenteric artery: normal values in different BMI categories

Abstract: The aortomesenteric angle and distance significantly correlate with BMI in normal population. The mean values, we report, may be used as normal values to help reach the diagnosis of superior mesenteric artery syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
0
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 20 publications
11
86
0
15
Order By: Relevance
“…This is in concordance with the findings of the study performed by Ozkurt et al [3] who concluded that the aortomesenteric angle and distance significantly correlate with BMI in normal population. Additionally, we also observe strong positive correlation between angle and distance.…”
Section: Mean and Standard Deviationssupporting
confidence: 93%
“…This is in concordance with the findings of the study performed by Ozkurt et al [3] who concluded that the aortomesenteric angle and distance significantly correlate with BMI in normal population. Additionally, we also observe strong positive correlation between angle and distance.…”
Section: Mean and Standard Deviationssupporting
confidence: 93%
“…The rapid increase in body height and the maturation of the vertebral bodies during puberty is resulting with decrease in the angle between the superior mesenteric artery and aorta. A low body mass index has been shown to correlate positively with NCS [10] .…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…The study patient was thin and her abdominal pain was exaggerated by physical activities. Regarding anatomy, when the body is upstanding, visceral proptosis diminishes the angle between the SMA and aorta, heightens the hemodynamic response especially if there is decreased retroperitoneal and mesenteric fat tissue (10).…”
Section: Discussionmentioning
confidence: 99%